The switch from etanercept originator to SB4: data from a real-life experience on tolerability and persistence on treatment in joint inflammatory diseases. (October 2020) - Bruni, Cosimo; Gentileschi, Stefano; Pacini, Giovanni; Baldi, Caterina; Capassoni, Marco; Tofani, Lorenzo; Bardelli, Marco; Cometi, Laura; Cantarini, Luca; Nacci, Francesca; Vietri, Michele; Bartoli, Francesca; et al.
Aims: Switching from originator to biosimilar is part of current practice in inflammatory rheumatic musculoskeletal diseases (iRMDs) such as rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondylarthritis (axSpA), with evidences derived from both etanercept (ETN) to SB4-switching randomized controlled trials and real-life registries. We investigated the safety and treatment persistence of ETN/SB4 in a multi-iRMD cohort derived from two rheumatology departments in our region. Methods: Adult patients with iRMDs, treated with ETN for at least 6 months and switched to SB4 in stable clinical condition, were eligible for this retrospective evaluation. Retrospective data on adverse events, loss of efficacy and persistence on treatment were collected until latest available follow-up. Results: A total of 220 patients (85 RA, 81 PsA, 33 axSpA, 14 juvenile idiopathic arthritis and seven other conditions; 142 females, mean age 58 ± 7 years, disease duration 12 ± 4 years, ETN duration 7 ± 4 years) were enrolled, with median follow-up of 12.1 (9.7–15.8) months. A total of 50 patients (22.7%) presented with at least one adverse event, with 36 (16.4%) disease flares and 30 (13.6%: 11 for safety and 19 loss of efficacy) SB4 withdrawals. Cumulative SB4 treatment persistence was 99.1%, 88.6% and 64.6% at 6, 12 and 18 months respectively. Back-switch to ETN was performed in 17/30 cases, the remaining cases were managed with change of biologic disease modifying or conventional synthetic anti-rheumatic drug. Age was the only significant predictor of SB4 interruption at 6 months. Conclusion: Our real-life data confirm the safety profile of switching from ETN to SB4, with slightly higher treatment persistence rates compared with other real-life registries.